Efek Intermolecular Forces: Perubahan Physical Properties pada Campuran Premium dan Bio-Additive Orange Peel - Musyaroh, Musyaroh; Wijayanti, Widya; Sasongko, Mega Nur; Rizaldy, Ahmad Difal (Jurnal Rekayasa Mesin, 2021)
The addition of bio-additive in gasoline was needed in order to improve the anti-knock quality. The bio-additive used was orange peel in the form of essential oil. Nevertheless, it make any changes of fuel properties affecting standard compliances: physical properties, engine performances and exhaust gas emissions due to some main compound effects of orange oil; limonene up to 90%. The recent study aimed to analyze the blends of bio-additives and premium gasoline experimentally related to improve the fuel properties theoretically. By verifying the blends, they were tested at blending concentration ratio from 1% to 75%. For each blend, the physical properties; kinematic viscosity, density, and calorific value were measured using ASTM D 445, ASTM D 92, and ASTM D 250. The results show that the limonene gave many impacts on the change of properties fuel. Limonene is a non-polar compound with high intramolecular force intensity. It causes a spontaneous dipole and gave propagation effect on premium gasoline molecular compound. The effect influences dynamic molecular distribution by increasing the attractive force between opposite pole of premium gasoline and bio-additives blend. The decrease of intermolecular movement intensity will decrease the viscosity of the mixture. In contrary, the kinematic viscosity of the mixture will increase with increasing bio-additive concentration. In other pysical properties, the premium gasoline-bio-additive blends have low density at 1%, 5%, 10% and 25% addition concentration but it has high heating value of fuel blends.